Operation of ohmic Ti/Al/Pt/Au multilayer contacts to GaN at 600 °C in air - Hou, Minmin; Senesky, Debbie G. (Applied physics letters, 2014)
The high-temperature characteristics (at 600 °C) of Ti/Al/Pt/Au multilayer contacts to gallium nitride (GaN) in air are reported. Microfabricated circular-transfer-line-method test structures were subject to 10 h of thermal storage at 600 °C. Intermittent electrical characterization during thermal storage showed minimal variation in the contact resistance after 2 h and that the specific contact resistivity remained on the order of 10−5 Ω-cm2. In addition, the thermally stored multilayer contacts to GaN showed ohmic I-V characteristics when electrically probed at 600 °C. The microstructural analysis with atomic force microscopy showed minimal changes in surface roughness after thermal storage. Observations of the thermochemical reactions after thermal storage using Auger electron spectroscopy chemical depth profiling showed diffusion of Pt and minimal additional Al oxidation. The results support the use of Ti/Al/Pt/Au multilayer metallization for GaN-based sensors and electronic devices that will operate within a high-temperature and oxidizing ambient.